Exogenous dihydrosphingosine 1 phosphate mediates collagen synthesis in cardiac fibroblasts through JAK/STAT signalling and regulation of TIMP1 - Magaye, R.R.; Savira, F.; Hua, Y.; Xiong, X.; Huang, L.; Reid, Christopher; Flynn, B.; Kaye, D.; Liew, D.; Wang, B.H. (2020)
© 2020 Elsevier Inc.